P213 Lasiodiplodia theobromae: an emerging human pathogen. (20th September 2022) - Kanaujia, Rimjhim; Gupta, Sunita; Kaur, Harsimran; Kindo, Anupama J.; Shetty, Anjali; Marak, Rungmei; Rammohan, Ram; Singla, Nidhi; Capoor, Malini; Balajee, G.; Gopal, Lokeshwari; Rastogi, Vijaylatha; et al.
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM: Objectives: Lasiodiplodia theobromae is a dematiaceous fungus, rarely reported to cause infections in humans. This case-series was conducted to identify the potential risk-factors and spectrum of diseases caused by L. theobromae . Methods: We performed a retrospective analysis of all cases from which the isolates of the L. theobromae were accessioned at the National culture collection of pathogenic fungi (NCCPF), over the last 10 years (January 2012- March 2022). The isolates were retrieved and identified by conventional (colony morphology, color, and microscopic appearances) and molecular (sequencing of ITS1 region of ribosomal DNA) methods. In vitro antifungal susceptibility testing (AFST) was performed by microbroth dilution recommended by the Clinical and Laboratory Standards Institute (CLSI). (M38-A2). The clinical features, demographic details and outcome were recorded. Results: In 10 years, a total of 20 patients were identified. The median age of all cases was 39.5 (range: 13-71 years) and 75% were males. The most common clinical presentation was keratomycosis (12, 68.6%), followed by soft tissue/sub-cutaneous infection (3, 15%), rhinosinusitis (3, 15%), onychomycosis (1, 5%), and pneumonia (1, 5%). Most patients were immunocompetent (85%). Among immunocompromised, two patients had acute myeloid leukemia and developed fungal rhinosinusitis while one patient of post-renal transplant on immunosuppressants developed subcutaneous tissue infection in the interscapular region. The fourth patient had decompensated alcoholic hepatitis, encephalopathy, sepsis, and developed pneumonia while he was on mechanical ventilation. Among the various potential risk factors associated with keratomycosis, the most common were, accidental trauma wounds (9, 45%), and mosquito bite in the eye in one patient. The culture on Sabouraud's dextrose agar (SDA) revealed the growth of black mycelial fungus (Fig. 1a). The lactophenol cotton blue (LCB) mount revealed the presence of only dematiaceous septate hyphae which failed to sporulate (Fig. 1b). All the isolates were confirmed by sequencing of ITS (internal transcribed spacer) region of the rDNA using universal primers ITS1 and ITS2. In vitro antifungal susceptibility testing (AFST) was performed using a broth microdilution (BMD) method which revealed variable MIC ( μ g/ml), i.e., amphotericin (1-2), voriconazole (0.25-2), itraconazole (8-16), posaconazole (1-2). All patients improved on therapy except one patient who succumbed to death due to pneumonia. Conclusion: Lasiodiplodia theobromae is an emerging cause of human infections in both immunocompetent and immunosuppressed individuals. It is often difficult to identify due to lack of sporulation making morphological identification challenging. Hence, prompt suspicion and rapid diagnosis with guided therapy are necessary for a better outcome.